Association of Serum High Sensitivity C-Reactive Protein with Insulin Resistance in Patients with Type-ΙΙ Diabetes Mellitus - Hossain, Nadia; Haque, Mahmudul; Karmakar, Pijush; Chowdhury, Hasan Murad; Barua, Prasun; Hoque, Asma; Mazhar, Aklima (Eastern Medical College Journal, 2022)
Background: Insulin resistance (IR) is the major event in type-ΙΙ diabetes mellitus followed by an increasing degree of β-cell dysfunction. Chronic inflammation is the driving force for IR and type-ΙΙ DM. The process of inflammation induces hepatic synthesis of high sensitivity C-reactive protein (an acute-phase protein) which plays a role in IR. The study was undertaken to find out the association of serum hs-CRP with insulin resistance in patients with type-ΙΙ diabetes mellitus. Methodology: A hospital-based observational study was carried out in the Outpatient Department of Endocrinology, Chittagong Medical College Hospital and Department of Biochemistry, Chittagong Medical College. A total of 126 patients with type-II diabetes mellitus aged 40-64 years were included by non-probability consecutive sampling technique. Serum hs-CRP, fasting serum insulin was estimated. IR was calculated by using the Homeostasis Model Assessment of Insulin Resistance index (HOMA-IR). Results: The mean serum hs-CRP level was 9.1 ± 0.36 mg/L in patients with type-II DM. Serum hs-CRP was significantly associated with insulin resistance and positively correlated with HOMA-IR in type-II diabetics. Body mass index (BMI) as one of the key indicators of insulin resistance was also associated with serum hs-CRP in this study population. Additionally serum hs-CRP was correlated positively with BMI and fasting serum insulin in patients with type-II DM. Conclusion: The results of this study concluded that increased serum hs-CRP was well associated and positively correlated with insulin resistance and its parameters signifying a possible role of subclinical inflammation in IR among patients with type-II diabetes mellitus. EMCJ. January 2022; 7(1): 15-20